Assessing Media and Security Agencies Relationship in Governance of Niger Delta, Nigeria - Akpan Udo (Goodwood Publishing, 2022)
Purpose: This work is an assessment of the relationship between media and security agencies in the Niger Delta region, Nigeria. The objectives were to assess reasons for frequent clashes between media and security agencies against press freedom while also suggesting measures of reducing face-offs. Research methodology: The research was a thorough opinion survey of 19,215,351 persons through a sample size of 400 persons in four states of the Niger Delta region of Nigeria. The states taken were Akwa Ibom, Delta, Cross River, and Rivers states. 400 questionnaires were distributed to residents for answers on the variables of the research. The social responsibility and media authoritarian theories were adopted in a theoretical framework. Results: The collated data from 375 persons representing 94 % against 25 persons or 6%, shows that the clash between media and the security agencies was very regular as security agencies noticeably enforce fear and intimidation at events. Limitations: The study was limited to only four states of Akwa Ibom, Delta, Cross River, and Rivers states out of nine states that make up the Niger Delta region of Nigeria. Contribution: The media and the security agencies should maintain practitioners’ regular training to keep abreast of democratic human rights and ethics in the discharge of duties. The present study will also theoretically contribute to the academic and theoretical richness as well as promote the culture and literature of social responsibility in the field of communication, governance, social civic service, and especially in the field of media literacy. It has effective significance and requisites.